A sustainable and green method for controlling acidic corrosion on mild steel using leaves of Araucaria heterophylla - Vanshika Singh; Sudesh Kumar; Ashish Sihmar; Hariom Dahiya; Jyoti Rani; Suresh Kumar; Gholamreza Abdi; Maryam Abbasi Tarighat (Scientific Reports)
Abstract There are several studies that announce the inhibitory behavior of this sort of substance to strengthen the shield of metals, which is one of the positive benefits of green inhibitors. In the current investigation, Araucaria heterophylla studied as a green corrosion inhibitor to avert the mild steel during the acidic cleaning. The examination of this plant’s ability to control corrosion at different concentrations in the acidic solution used certain expert measures. The electrochemical results suggested that Araucaria heterophylla had a stronger inhibitory effect on mild steel protection from corrosion. After 12 h of immersion, 1000 ppm of A. heterophylla extract produced corrosion inhibition efficacy (about 83.94%). According to the polarization outcomes, the mild steel corrosion current density dramatically decreased with the addition of Araucaria heterophylla extract, going from 1.08 μA/cm2 for the sample without inhibitor to 0.17 μA/cm2 for the sample having 1000 ppm inhibitor and according to electrochemical study the inhibition efficiency was found around 83%. Flavonoids were found in the plant’s leaves according to the high-performance thin-layer chromatography profile. The FTIR picks analysis like N–H stretching secondary amine (3337.07 cm−1), CO–O–C–O stretching anhydride (1022.64 cm−1) defined that functional groups and heteroatom were present. By the help of a GC–MS, the suggested inhibitor’s components were identified. Scanning electron microscopy suggests that a thin layer or passive film form on the surface. Quantum chemical calculation also supports the experimental results.